Mechanism of Organization and Development of a Cluster - Крістіна Унгур (Історико-політичні проблеми сучасного світу)
The latest trends of integration of the Central and Eastern Europe countries in the global economy increase the need for regional specialization and for the assertion on the markets through competitive advantages based on innovation, knowledge transfer and a rational use of resources. A certainway to meet these needs is to create clusters. This paper focuses on studying the principles and mechanisms of organizing a cluster and aims at developing a functional cluster creation and development algorithm. This paper deals with the study of the principles and mechanisms of cluster organization and aims at the development of a functional cluster creation and development algorithm. By using the logical reasoning method, bibliographic research and indirect observation, we have developed a mechanism of a cluster organization based on three basic stages: preparation, initiation and development. The knowledge and efficient implementation of this algorithm can help to create a network of innovation clusters capable to bring regional economic benefits. The mechanism proposed in this paper can be used in the promotion of cluster initiatives in all countries of Central and Eastern Europe, including Moldova, Ukraine and Romania.